Global priority DBA using fuzzy logic in Ethernet PON - Radzi N.A.M.; Din N.Md.; Majid Mohd.S.A.; Al-Mansoori M.H. (2023)
In order to fully optimize the bandwidth in upstream Ethernet passive optical network, dynamic bandwidth allocation (DBA) algorithm is used to allocate the bandwidth efficiently. In this paper, DBA algorithm that can support global priority is used to ensure the quality of service. Fuzzy logic is incorporated for the first time in the global priority DBA to reduce the packet loss as low as 13% and reduce the Expedited Forwarding, Assured Forwarding and Best Effort delay up to 31%, 19% and 13%, respectively if compared to Min's DBA and EDBA algorithms. 2011 IEEE.